The reply of the Finnish Estates adopted at the extraordinary Diet of 1899 to the proposals of His Imperial Majesty Nicholas II, Grand Duke of Finland, for a new Military Service Law in Finland. Transl. from the Swedish (Eyre and Spottiswoode, 1900)
With index.